Implementasi pendidikan karakter melalui pembiasaan dalam meningkatkan sikap disiplin peserta didik - Riasinta, Ni Kadek Ratna; Wayan Widiana, I; Luh Gede Erni Sulindawati, Ni (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
Most previous research has focused on specific outcomes, such as discipline or moral behavior, rather than examining program implementation holistically. Addressing this gap, the present study evaluates the effectiveness of the 7 Habits of Great Indonesian Children Program at SMP Negeri 1 Kuta Utara using the CIPP (Context, Input, Process, Product) evaluation model. This study employed a quantitative evaluative design involving 90 students selected through purposive sampling. Data were collected through Likert-scale questionnaires, observations, and documentation, and analyzed using descriptive statistics, T-Score calculations, and the Glickman Quadrant to determine the program’s effectiveness position. The findings indicate that the program demonstrates a high level of effectiveness across all four CIPP components. The context evaluation shows strong alignment with the school’s vision and character development goals. The input component reflects adequate resource support and student readiness. The process component reveals consistent implementation through structured daily habituation practices. The product component indicates measurable positive changes in students’ disciplined, religious, and socially responsible behaviors. Based on the Glickman Quadrant analysis, the program is positioned in Quadrant I (Very Good), suggesting that the integration of environmental preparedness, teacher role modeling, and sustained habituation contributes meaningfully to character development. This study contributes to the literature by providing a holistic, model-based evaluation of a multi-habit character education program within the Indonesian secondary school context. However, the findings are limited to one school setting and rely primarily on self-reported data, which may affect generalizability. Future studies are recommended to incorporate comparative designs and longitudinal data to better assess long-term program impact.